Effectiveness of insider trading law in South Africa's equity market: the mergers and acquisitions example - Mitchell, Justin William Eric (My University, 2015)
Shares in takeover target companies listed on the JSE have historically earned abnormal returns in the days preceding the public announcements of planned takeovers. This has not been tested since the enforcement of insider trading law in South Africa. Furthermore, it is unclear whether the existence of such abnormal returns occur as a result of legal market activity or if it infers illegal insider trading. The extent of Average Cumulative Abnormal Returns (“ACAR”) that occur in the 21 days preceding the announcement of a takeover is established for a sample of 57 takeovers that transpired between 2004 and 2014. ACAR establishes the average abnormal return that each takeover target company accumulates during the 21 day event window. 30 Personal Interviews offer insight into the causes of Cumulative Abnormal Returns (“CAR”) preceding each takeover announcement. Results indicate that shares in takeover target companies accumulate significant ACAR (9.03%) during the 21 trading days preceding the first public announcement of a takeover. Interview findings include the existence of plausible legal explanations for instances of CAR, which contradicts the suggestion that ACAR constitutes prima facie evidence of illegal insider trading. However, the study resolved that the occurrences of CAR were as a result of both legal market activity and illegal insider trading occurring after widespread information leaks. The existence of significant ACAR – more so than in previous South African studies – highlights the need for further investigation into the effectiveness of South African insider trading law in preventing illegal insider trading preceding the announcement of planned takeovers.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.